Produtividade na indústria brasileira no passado recente: um estudo dos diferenciais intersetoriais - João Saboia (Economia Aplicada, 2004)
This paper discusses the recent evolution of labor productivity in the Brazilian manufacturing and mineral extractive industry. It shows an increase in the productivity gap among industrial sectors from 1985 to 2000. The analysis is developed from different perspectives such as the type of industry, the size of the enterprises and the productivity level. It is identified an inverse relation between the behavior of employment and productivity. This result confirms the difficulties to simultaneously increase productivity and employment in the Brazilian industry. The paper makes use oftwo data sources - the Industrial Census of 1985 and the Annual Industrial Survey (Pesquisa Industrial Anual) from 1996 to 2000.